Effect of International Trade Agreements on National Sovereignty in Kenya - Ndabui, Phillis (American Journal of International Relations, 2024)
Purpose: The aim of the study was to assess the effect of international trade agreements on national sovereignty in Kenya. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that international trade agreements enhance economic opportunities by opening markets, fostering trade relations, and promoting economic growth. They create frameworks for international cooperation, allowing countries to benefit from shared resources, knowledge, and investments. However, these agreements can also limit a nation's ability to make independent decisions, as countries must adhere to international rules and regulations that may conflict with domestic policies or priorities. In some cases, trade agreements may force countries to compromise on sensitive issues like labor standards, environmental protections, and intellectual property rights, reducing the autonomy of national governments in these areas. While trade agreements encourage globalization and economic interdependence, they often lead to debates over the balance between economic benefits and the preservation of national sovereignty. Implications to Theory, Practice and Policy: Realism theory, liberal institutionalism and dependency theory may be used to anchor future studies on assessing the effect of international trade agreements on national sovereignty in Kenya. There should be a focus on negotiating provisions that allow for greater flexibility and adaptation of domestic laws without compromising sovereignty. Policymakers should design and implement trade policies that maintain a balance between economic integration and sovereignty preservation.